PENGARUH PROMOTION, PERCEIVED DEFFERENTIATION DAN BRAND TRUST TERHADAP BRAND LOYALTY PADA PRODUK FASHION AEROSTREET - Susanto, Dimas Audy; Aprilia, Natasya Eka; Putri, Nadya Kusuma (Universitas Tanjungpura, 2024)
AeroStreet is a regional fashion brand that captivates people with its contemporary urban aesthetics and competitive pricing. This study seeks to examine the impact of promotions, perceived difference, and brand trust on loyalty to the AeroStreet brand. A quantitative methodology was employed utilizing an online questionnaire survey, which had 145 participants. Data were examined utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess validity, reliability, and interrelationships among variables. The survey employs a 1-5 Likert scale to assess respondents' perceptions. The research findings indicate that promotions do not significantly affect brand loyalty. Product differentiation is crucial, since consumers who see AeroStreet items as distinctive are likely to exhibit loyalty. Moreover, brand trust significantly impacts loyalty, as consumers who have confidence in a brand's quality and reputation exhibit greater loyalty. This study offers insights into the formulation of marketing strategies within the local fashion sector.